Silver nanowire elastic composite material and preparation method and application thereof
By using silver nanowire elastic composite materials, the problem of insufficient flexibility caused by the rigidity of the probe of traditional ultrasonic equipment is solved, and high-frequency signal processing and high-resolution imaging of flexible ultrasonic transducers are realized, improving the accuracy and reliability of detection.
Patent Information
- Application Number
- CN202510049805.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Traditional ultrasound equipment uses rigid probes, which have limited flexibility, difficulty in conducting long-term continuous monitoring, and relatively poor patient comfort.
A silver nanowire elastic composite material is used to prepare a flexible material with good conductivity and excellent tensileability by combining water-soluble salt particles or sugar particles as templates with silver nanowires and elastic materials, and is used to prepare a flexible ultrasonic transducer backing layer.
The wider frequency signal processing of ultrasonic transducers is realized, which improves imaging resolution and penetration depth, simplifies the structure, reduces manufacturing difficulty and cost, and improves detection accuracy and reliability.
Smart Images

Figure HDA0005239641330000011 
Figure HDA0005239641330000012 
Figure HDA0005239641330000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible devices, and in particular to a silver nanowire elastic composite material and a preparation method and application thereof. Background Art
[0002] Ultrasound imaging has been widely used in the medical field due to its advantages such as high resolution, low cost, real-time imaging, no radiation, non-invasiveness and high safety.
[0003] The ultrasonic transducer adopts a multilayer structure, including a matching layer, a piezoelectric layer, an electrode layer, a backing layer and a packaging layer. The backing layer optimizes the impedance mismatch between the piezoelectric layer and the air, absorbs the backscattered energy as much as possible, and suppresses the ringing effect, thereby improving the ultrasonic imaging effect. The main design parameters of the backing layer include the acoustic attenuation coefficient and the acoustic impedance. Since the acoustic impedance of the backing layer affects the sensitivity of the sensor, a higher acoustic impedance can increase the sensitivity, but reduce the bandwidth; if the acoustic impedance is reduced, it has a higher attenuation, increases the bandwidth, but reduces the sensitivity. Therefore, it is necessary to set the parameters of the backing layer according to the design needs. The preparation materials of the backing layer can be roughly divided into three categories: light backings are often made of polymers such as rubber and resin; medium backings are mostly made of epoxy resin and alumina powder; heavy backings are made of epoxy resin mixed with tungsten powder. These preparation materials can meet most traditional transducer designs, but with the continuous update and iteration of researchers on ultrasonic equipment, the hardware requirements for ultrasonic equipment are constantly increasing. For example, high-frequency ultrasound imaging, which uses ultrasound with a frequency of more than 20MHz for imaging, can obtain shorter wavelengths due to high frequencies, so that it is less diffracted and scattered during propagation, and can reflect and focus more accurately, so as to detect smaller tissue structures, such as intravascular ultrasound. However, due to the short wavelength, the backing layer is required to have high attenuation capability. Kim et al. made a high-attenuation backing layer made of glass beads, polyamide resin and tungsten powder. This design improves the problem that the traditional backing needs to increase the size and thickness to achieve the ideal attenuation effect. The addition of glass beads can also increase the attenuation coefficient through its scattering and absorption. Such a design meets the design requirements of high-frequency ultrasound imaging, which requires a smaller transducer to concentrate energy for effective emission and reception of high-frequency sound waves. Siewe et al. also provided a multiphase metal backing layer made of sintered bronze and tin according to the high-frequency design requirements. In the pulse echo test, no echo was detected at the back of the backing, and it has higher sensitivity than traditional materials. These emerging backing layer designs have improved the physical structure of the ultrasonic transducer to a certain extent, improved the imaging effect, and made the application of ultrasound more extensive.
[0004] However, traditional ultrasound devices usually use rigid probes and require a coupling agent to be applied between the probe and the skin to improve image quality. However, such devices rely on manual operation by professional medical staff, have limited flexibility, are difficult to perform long-term continuous monitoring, and have relatively poor patient comfort. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a silver nanowire elastic composite material and a preparation method and use thereof, so as to solve the problems in the prior art.
[0006] To achieve the above-mentioned object and other related objects, the present invention first provides a method for preparing a silver nanowire elastic composite material, the preparation method comprising the following steps:
[0007] 1) Mixing a template material with water to prepare a template, and drying the template to obtain a water-free template; the template material is a water-soluble salt particle or a water-soluble sugar particle; the diameter of the water-soluble sugar particle or the water-soluble salt particle is 100 to 800
[0008] μm;
[0009] 2) performing surface modification treatment on the anhydrous template prepared in step 1), and then coating the surface of the anhydrous template with a silver nanowire solution to prepare a silver nanowire-anhydrous template complex;
[0010] 3) mixing the liquid elastic material with the silver nanowires and the waterless template complex prepared in step 2) and letting the mixture stand for curing to obtain a silver nanowire-waterless template-elastic material complex; placing the silver nanowire-waterless template-elastic material complex in water to dissolve the template material and generate a porous structure, thereby obtaining the silver nanowire elastic composite material.
[0011] The present invention also provides a silver nanowire elastic composite material, which is prepared by the above method.
[0012] The present invention also provides use of the silver nanowire elastic composite material in preparing a flexible ultrasonic transducer backing layer.
[0013] The present invention also provides use of the silver nanowire elastic composite material in preparing a flexible electrode.
[0014] The present invention also provides use of the silver nanowire elastic composite material in preparing a flexible displacement sensor.
[0015] The present invention also provides a flexible ultrasonic transducer, wherein the flexible ultrasonic transducer comprises the silver nanowire elastic composite material.
[0016] The present invention also provides a flexible electrode, wherein the flexible electrode comprises the silver nanowire elastic composite material.
[0017] The present invention also provides a flexible displacement sensor, wherein the flexible displacement sensor comprises the silver nanowire elastic composite material.
[0018] As described above, the silver nanowire elastic composite material and the preparation method and use thereof of the present invention have the following beneficial effects:
[0019] 1) The prepared silver nanowire elastic composite material is flexible and stretchable (>100% strain) and conductive, with a resistance of less than 10 ohms;
[0020] 2) This method uses a water-soluble material template and a drop coating method to assemble the silver nanowire network into a three-dimensional interconnected porous structure, and with the help of the composite of elastic material and silver nanowires, a flexible material with good conductivity and good stretchability that meets the functional requirements of the backing layer is formed;
[0021] 3) The prepared silver nanowire elastic composite material is used as the backing layer of the ultrasonic transducer, which enables the super energy transducer to process a wider range of frequency signals, improve higher imaging resolution and deeper penetration depth, capture more subtle signal changes, provide richer information, and help improve the accuracy and reliability of detection;
[0022] 4) The prepared silver nanowire elastic composite material is used as the backing layer of the ultrasonic transducer, which can attenuate the sound wave signal and meet the design requirements of the material's stretchability. At the same time, due to the conductivity of silver, the backing layer can be used as a transducer electrode, simplifying the structure and reducing the manufacturing difficulty and cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Shown is a schematic diagram of the salt template prepared in Example 1 of the present invention.
[0024] Figure 2 It is an enlarged schematic diagram of the salt template prepared in Example 1 of the present invention. The overall size is 1.5 cm×1.5 cm.
[0025] Figure 3 It is a schematic diagram showing the porous structure formed by the silver nanowire-Ecoflex elastic composite material after the salt particles are melted in Example 1 of the present invention.
[0026] Figure 4 Shown is the overall processing flow chart of the nanowire-Ecoflex elastic composite material in Example 1 of the present invention.
[0027] Figure 5The structure schematic diagram of the composite material used as the backing layer in the flexible ultrasonic transducer in Application Example 1 of the present invention is shown. In the figure: 1 represents the silver nanowire elastic composite material backing layer; 2 is the piezoelectric material layer; 3 is the flexible matching layer.
[0028] Figure 6 Shown is the impulse response graph of an ultrasonic transducer without a backing layer; -6dB bandwidth 17.9%.
[0029] Figure 7 Shown is the impulse response of an ultrasonic transducer with a conventional E-solder backing layer; -6dB bandwidth 27.5%.
[0030] Figure 8 The pulse response diagram of the ultrasonic transducer using the silver nanowire elastic composite material prepared in the example as the backing layer is shown; -6dB bandwidth is 46.9%. DETAILED DESCRIPTION
[0031] The present invention first provides a method for preparing a silver nanowire elastic composite material, the preparation method comprising the following steps:
[0032] 1) Mixing a template material with water to prepare a template, and drying the template to obtain a water-free template; the template material is a water-soluble salt particle or a water-soluble sugar particle; the diameter of the water-soluble sugar particle or the water-soluble salt particle is 100 to 800
[0033] μm;
[0034] 2) performing surface modification treatment on the anhydrous template prepared in step 1), and then coating the surface of the anhydrous template with a silver nanowire solution to prepare a silver nanowire-anhydrous template complex;
[0035] 3) mixing the liquid elastic material with the silver nanowires and the waterless template complex prepared in step 2) and letting the mixture stand for curing to obtain a silver nanowire-waterless template-elastic material complex; placing the silver nanowire-waterless template-elastic material complex in water to dissolve the template material and generate a porous structure, thereby obtaining the silver nanowire elastic composite material.
[0036] In certain embodiments of the present invention, in step 1), the diameter of the water-soluble sugar particles or water-soluble salt particles is 200-600 μm.
[0037] In certain embodiments of the present invention, in step 1), the water-soluble salt particles are selected from organic salts or inorganic salts.
[0038] In certain embodiments of the present invention, in step 1), the organic salt is selected from an organic sodium salt or an organic potassium salt.
[0039] In a preferred embodiment of the present invention, in step 1), the organic sodium salt is sodium acetate or sodium citrate.
[0040] In certain embodiments of the present invention, in step 1), the inorganic salt is selected from an inorganic sodium salt or an inorganic potassium salt.
[0041] In a preferred embodiment of the present invention, in step 1), the inorganic sodium salt is sodium chloride, sodium sulfate or sodium nitrate.
[0042] In certain embodiments of the present invention, in step 1), the water-soluble sugar particles are selected from sucrose particles or granulated sugar particles.
[0043] In a preferred embodiment of the present invention, in step 1), the average diameter of the sucrose particles is 300-500 μm.
[0044] In a preferred embodiment of the present invention, in step 1), the average diameter of the granulated sugar particles is 500-600 μm.
[0045] In certain embodiments of the present invention, in step 1), the mass ratio of the template material to water is (20-60):1.
[0046] In certain embodiments of the present invention, the mass ratio of the template material to water is selected from any of the following ranges: (30-35):1, (35-40):1, (40-45):1, (45-50):1.
[0047] In certain embodiments of the present invention, in step 1), the drying temperature is 40-60°C.
[0048] In certain embodiments of the present invention, in step 1), the temperature of the drying treatment is selected from any of the following ranges: 40-45°C, 45-50°C, 50-55°C, 55-60°C.
[0049] In certain embodiments of the present invention, in step 2), the surface modification is to improve the surface energy and interface compatibility of the anhydrous template.
[0050] In certain embodiments of the present invention, in step 2), the device for performing surface modification treatment on the waterless template is a plasma processor. The technology of treating the waterless template with a plasma processor can be realized by existing technology.
[0051] Plasma treatment is a process in which active particles in the plasma (such as ions, electrons, free radicals, excited molecules, etc.) interact with the surface of the material, thereby changing the physical and chemical properties of the material surface. This treatment method can achieve the purposes of cleaning the surface, increasing surface energy, and changing surface morphology.
[0052] In certain embodiments of the present invention, in step 2), the experimental temperature for coating the nanowire solution on the surface of the water-free template is 50-120°C.
[0053] In certain embodiments of the present invention, in step 2), the experimental temperature is selected from any of the following ranges: 90-95°C, 95-100°C, 100-105°C, 105-110°C.
[0054] In certain embodiments of the present invention, in step 2), the concentration of the silver nanowire solution is 0.5-4 mg / mL. The concentration of the silver nanowire solution is selected from any of the following ranges: 0.5-0.8 mg / mL, 0.8-1.1 mg / mL, 1.1-1.4 mg / mL, 1.4-1.7 mg / mL, 1.7-2 mg / mL.
[0055] In certain embodiments of the present invention, in step 2), the silver nanowire solution is obtained by mixing silver nanowires with ethanol.
[0056] In certain embodiments of the present invention, in step 2), the average diameter of the silver nanowires is 100-150 nm. The average diameter of the silver nanowires is selected from any of the following ranges: 100-110 nm, 110-120 nm, 120-130 nm, 130-140 nm, 140-150 nm.
[0057] In certain embodiments of the present invention, in step 2), the average length of the silver nanowires is 10-30 μm. The average length of the silver nanowires is selected from any of the following ranges: 10-15 μm, 15-20 μm, 20-25 μm, 25-30 μm.
[0058] In certain embodiments of the present invention, step 2) further comprises coating the silver nanowire solution on the surface of the water-free template until the surface conductivity of the water-free template after the solvent evaporates is greater than 100 S / cm.
[0059] The specific operation steps are as follows: coating the silver nanowire solution on the surface of the waterless template, waiting for the solvent to evaporate, and then measuring the conductivity of the surface of the waterless template. If the surface of the waterless template is conductive after the solvent evaporates, directly proceed to step 3). If the surface of the waterless template is not conductive after the solvent evaporates, the silver nanowire solution is coated on the surface of the waterless template multiple times until the conductivity of the surface of the waterless template after the solvent evaporates is greater than 100S / cm.
[0060] In certain embodiments of the present invention, in step 3), the base of the elastic material is generally a polymer material.
[0061] In certain embodiments of the present invention, in step 3), the polymer material is selected from one or more of Ecoflex, polyimide (PI), polyethylene (PE), polyurethane (PU) or polydimethylsiloxane (PDMS).
[0062] In a preferred embodiment of the present invention, the elastic material is Ecoflex. The Ecoflex consists of two parts: A glue and B glue.
[0063] In certain embodiments of the present invention, the Ecoflex is prepared by mixing glue A and glue B.
[0064] In a preferred embodiment of the present invention, the mass ratio of glue A to glue B is 1:1.
[0065] In a preferred embodiment of the present invention, the elastic material is PDMS. The PDMS comprises two components: a prepolymer A and a cross-linking agent B.
[0066] In a specific embodiment of the present invention, the PDMS is obtained by mixing prepolymer A and cross-linking agent B in a mass ratio of 4:1.
[0067] In certain embodiments of the present invention, in step 3), the liquid elastic material is mixed with the silver nanowire-anhydrous template complex prepared in step 2) until the elastic material completely covers the surface of the silver nanowire-anhydrous template complex.
[0068] In certain embodiments of the present invention, in step 3), the standing is standing in a vacuum. Placing in a vacuum environment can promote the liquid elastic material to penetrate into the pores of the template.
[0069] In certain embodiments of the present invention, in step 3), the curing time is 4 to 8 hours. The curing time is selected from any of the following ranges: 4 to 5 hours, 5 to 6 hours, 6 to 7 hours, and 7 to 8 hours.
[0070] In certain embodiments of the present invention, in step 3), the curing temperature is 20-40°C.
[0071] In certain embodiments of the present invention, in step 3), the silver nanowire-anhydrous template-elastic material complex is placed in pure water to dissolve the water-soluble template material.
[0072] In certain embodiments of the present invention, in step 3), the silver nanowire-anhydrous template-elastic material composite is placed in water at 40-80°C to dissolve the water-soluble template material. The temperature of the water is selected from any of the following ranges: 40-50°C, 50-60°C, 60-70°C, 70-80°C.
[0073] In certain embodiments of the present invention, in step 3), the dissolution time is 12 hours to 3 days. The dissolution time is selected from any of the following ranges: 12 hours to 24 hours, 24 hours to 2 days, and 2 days to 3 days.
[0074] In certain embodiments of the present invention, step 3) further comprises removing the elastic material attached to the surface of the silver nanowire elastic composite material after the anhydrous template is completely dissolved.
[0075] In certain embodiments of the present invention, step 3) further comprises cutting the prepared silver nanowire elastic composite material into a desired shape.
[0076] The present invention also provides a silver nanowire elastic composite material, which is prepared by the above method.
[0077] The present invention also provides use of the silver nanowire elastic composite material in preparing a flexible ultrasonic transducer backing layer.
[0078] The present invention also provides use of the silver nanowire elastic composite material in preparing a flexible electrode.
[0079] In the present invention, the flexible electrode can be used as an electrode layer of a flexible ultrasonic transducer, and can also be applied to any other electrode occasions.
[0080] The present invention also provides use of the silver nanowire elastic composite material in preparing a flexible displacement sensor.
[0081] The present invention also provides a flexible ultrasonic transducer, wherein the flexible ultrasonic transducer comprises the silver nanowire elastic composite material.
[0082] In certain embodiments of the present invention, the silver nanowire elastic composite material can be used as both a backing layer and an electrode layer of a flexible ultrasonic transducer.
[0083] The present invention also provides a flexible electrode, wherein the flexible electrode comprises the silver nanowire elastic composite material.
[0084] The present invention also provides a flexible displacement sensor, wherein the flexible displacement sensor comprises the silver nanowire elastic composite material.
[0085] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0086] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing the specific embodiments rather than for limiting the scope of protection of the present invention; in the present specification and claims, unless otherwise expressly stated herein, the singular forms "a", "an" and "the" include plural forms.
[0087] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0088] Any technology not specifically disclosed in the present invention may adopt existing technology.
[0089] Example 1
[0090] First, NaCl salt particles with a diameter of 281 μm and laboratory pure water were selected and mixed in a mass ratio of 40:1 to make a water-soluble salt template. The salt template was placed in an oven and heated and dried at 45°C to remove the added water to form an anhydrous salt template.
[0091] Subsequently, the surface of the salt template was treated with a plasma processor, and then a dropper was used to draw a 1 mg / mL silver nanowire solution (average diameter of the silver nanowire was 120 nm, average length was 20 μm) diluted with ethanol and applied to the anhydrous salt template on a heating table at 90°C. After coating, the ethanol was allowed to evaporate, and this process was repeated until the surface of the anhydrous salt template was measured to be conductive.
[0092] Then, Ecoflex made by mixing A and B glue in a mass ratio of 1:1 was completely coated on the upper surface of the silver nanowire-anhydrous salt template complex, and the culture dish containing the silver nanowire-anhydrous salt template-Ecoflex was placed in a vacuum to promote the penetration of liquid Ecoflex into the pores of the template. In order to cure Ecoflex, it was cured at room temperature for 6 hours. The cured silver nanowire-anhydrous salt template-Ecoflex was immersed in a beaker filled with 60°C pure water, and the beaker was placed on a heating table at 80°C to dissolve the salt. After 24 hours, the salt template was completely dissolved and a porous structure was generated. The Ecoflex attached to the surface was removed with tweezers;
[0093] Finally, the prepared silver nanowire elastic composite material is cut into a desired shape.
[0094] Example 2
[0095] First, sodium citrate particles with a diameter of 327 μm and laboratory pure water were selected and mixed in a mass ratio of 30:1 to prepare a water-soluble salt template, which was then placed in an oven and heated and dried at 50°C to remove the added water to form an anhydrous salt template.
[0096] Subsequently, the surface of the salt template was treated with a plasma processor, and then a dropper was used to draw a 2 mg / mL silver nanowire solution (average diameter of the silver nanowire was 100 nm, average length was 30 μm) diluted with ethanol and applied to the anhydrous salt template on a heating table at 60°C. After coating, the ethanol was allowed to evaporate, and this process was repeated until the surface of the anhydrous salt template was measured to be conductive.
[0097] Then, the PDMS prepared by mixing prepolymer A and crosslinker B in a mass ratio of 4:1 was completely coated on the upper surface of the silver nanowire-anhydrous salt template complex, and the culture dish containing the silver nanowire-anhydrous salt template-PDMS was placed in a vacuum to promote the penetration of liquid PDMS into the pores of the template. In order to cure the PDMS, it was cured at room temperature for 8 hours. The cured silver nanowire-anhydrous salt template-PDMS was immersed in a beaker filled with 80°C pure water, and the beaker was placed on a heating table at 100°C to dissolve the salt. After 12 hours, the salt template was completely dissolved and a porous structure was generated. The PDMS attached to the surface was removed with tweezers;
[0098] Finally, the prepared silver nanowire elastic composite material is cut into a desired shape.
[0099] Example 3
[0100] First, ordinary sucrose particles with a diameter of 401 μm and laboratory pure water were selected and mixed in a mass ratio of 50:1 to prepare a water-soluble salt template, which was then placed in an oven and heated and dried at 60°C to remove the added water to form an anhydrous salt template.
[0101] Subsequently, the surface of the salt template was treated with a plasma processor, and then a dropper was used to draw a 3 mg / mL silver nanowire solution (average diameter of the silver nanowire was 200 nm, average length was 40 μm) diluted with ethanol and applied to the anhydrous salt template on a heating table at 80°C. After coating, the ethanol was allowed to evaporate, and this process was repeated until the surface of the anhydrous salt template was measured to be conductive.
[0102] Then, Ecoflex made by mixing A and B glue in a mass ratio of 1:1 was completely coated on the upper surface of the silver nanowire-anhydrous salt template complex, and the culture dish containing the silver nanowire-anhydrous salt template-Ecoflex was placed in a vacuum to promote the penetration of liquid Ecoflex into the pores of the template. In order to cure Ecoflex, it was cured at room temperature for 4 hours. The cured silver nanowire-anhydrous salt template-Ecoflex was immersed in a beaker filled with 60°C pure water, and the beaker was placed on a heating table at 60°C to dissolve the salt. After 2 days, the salt template was completely dissolved and a porous structure was generated. The Ecoflex attached to the surface was removed with tweezers;
[0103] Finally, the prepared silver nanowire elastic composite material is cut into a desired shape.
[0104] Application Example 1
[0105] The silver nanowire elastic composite material prepared in Example 1 of the present invention is used as a backing layer in a flexible ultrasonic transducer. The resistance of the prepared silver nanowire elastic composite material backing layer is less than 10 ohms as measured by a multimeter. Experimental verification shows that the silver nanowire elastic composite material has high tensile properties (>100% strain) and good electrical conductivity. Compared with an ultrasonic transducer without a backing layer and an ultrasonic transducer with a traditional E-solder backing layer, the ultrasonic transducer with the material prepared in Example 1 as a backing layer has a wider bandwidth ( Figure 6 to Figure 8 ). Therefore, the silver nanowire elastomer composite material prepared by the method can be used as a backing layer of a wearable ultrasonic transducer and has high conductivity.
[0106] The above examples are for the purpose of illustrating the embodiments disclosed by the present invention and are not to be construed as limiting the present invention. In addition, the various modifications listed herein and the variations of the methods in the invention are obvious to those skilled in the art without departing from the scope and spirit of the present invention. Although the present invention has been specifically described in conjunction with various specific preferred embodiments of the present invention, it should be understood that the present invention should not be limited to these specific embodiments. In fact, various modifications as described above that are obvious to those skilled in the art to obtain the invention should be included within the scope of the present invention.
Claims
1. A method for preparing a silver nanowire elastic composite material, characterized in that: The preparation method comprises the following steps: 1) mixing a template material with water to prepare a template, and drying the template to obtain a water-free template; the template material is a water-soluble salt particle or a water-soluble sugar particle; the diameter of the water-soluble sugar particle or the water-soluble salt particle is 100 to 800 μm; 2) performing surface modification treatment on the anhydrous template prepared in step 1), and then coating the surface of the anhydrous template with a silver nanowire solution to prepare a silver nanowire-anhydrous template complex; 3) mixing the liquid elastic material with the silver nanowire-anhydrous template complex prepared in step 2) and letting it stand for solidification to obtain a silver nanowire-anhydrous template-elastic material complex; placing the silver nanowire-anhydrous template-elastic material complex in water to dissolve the template material and generate a porous structure, thereby obtaining the silver nanowire elastic composite material.
2. The preparation method according to claim 1, characterized in that: In step 1), any one or more of the following conditions are included: 11) The water-soluble salt particles are selected from organic salts or inorganic salts; preferably, the organic salt is selected from organic sodium salts or organic potassium salts; more preferably, the organic sodium salt is sodium citrate; preferably, the inorganic salt is selected from inorganic sodium salts or inorganic potassium salts; more preferably, the inorganic sodium salt is sodium chloride, sodium sulfate or sodium nitrate; 12) The water-soluble sugar particles are selected from sucrose particles or granulated sugar particles; 13) The mass ratio of the template material to water is 20 to 60:1; 14) The temperature of the drying treatment is 40-60°C.
3. The preparation method according to claim 1, characterized in that: In step 2), any one or more of the following conditions are included: 21) The surface modification is to improve the surface energy and interfacial compatibility of the anhydrous template; 22) The experimental temperature for coating the nanowire solution on the anhydrous template surface is 50-120°C; 23) The concentration of the silver nanowire solution is 0.5-4 mg / mL; 24) The silver nanowire solution is obtained by mixing silver nanowires with ethanol; 25) The average diameter of the silver nanowires in the silver nanowire solution is 100 to 150 nm; 26) The average length of the silver nanowires in the silver nanowire solution is 10 to 30 μm; 27) coating the silver nanowire solution on the surface of the water-free template until the surface conductivity of the water-free template after the solvent evaporates is greater than 100 S / cm.
4. The preparation method according to claim 1, characterized in that: In step 3), any one or more of the following conditions are included: 31) The elastic material is selected from one or more of Ecoflex, PI, PE or PDMS; preferably, the elastic material is Ecoflex; 32) the elastic material completely covers the surface of the silver nanowire-anhydrous template complex; 33) The said standing is standing in a vacuum; 34) The curing time is 4 to 8 hours; 35) The curing temperature is 20-40°C.
5. The preparation method according to claim 1, characterized in that: In step 3), any one or more of the following conditions are included: 36) placing the silver nanowire-anhydrous template-elastic material complex in water at 40-80° C. to dissolve the water-soluble template material; 37) The dissolution time is 12 hours to 3 days; 38) removing the elastic material attached to the surface of the silver nanowire elastic composite material after the anhydrous template is completely dissolved; 39) Cutting the prepared silver nanowire elastic composite material into desired shapes.
6. A silver nanowire elastic composite material, characterized in that: The silver nanowire elastic composite material is prepared by the preparation method described in any one of claims 1 to 5.
7. Use of the silver nanowire elastic composite material as claimed in claim 6 in preparing a flexible ultrasonic transducer backing layer, a flexible electrode and / or a flexible displacement sensor.
8. A flexible ultrasonic transducer, characterized in that: The flexible ultrasonic transducer comprises the silver nanowire elastic composite material as claimed in claim 6.
9. A flexible electrode, characterized in that: The flexible electrode comprises the silver nanowire elastic composite material as claimed in claim 6.
10. A flexible displacement sensor, characterized in that: The flexible displacement sensor comprises the silver nanowire elastic composite material as claimed in claim 6.
Citation Information
Patent Citations
Stretchable conductive composite and preparing method and application thereof
CN105038249A
Silver nanowire / organic silicon elastomer self-repairing flexible material, preparation method thereof and flexible sensor
CN112679964A
Porous flexible GNP / PDMS composite material, preparation method thereof and application of porous flexible GNP / PDMS composite material in strain sensor
CN113372609A
Preparation method of flexible resistance sensor based on silver nanowire material
CN116512731A
Nanowire complex and manufacturing method therefor
WO2019203492A1